Description and evaluation of an intraoral cervical plexus anesthetic technique. Issue 5 (10th April 2015) - Bitner, Daniel P.; Uzbelger Feldman, Daniel; Axx, Kevin; Albandar, Jasim M.
<x xml:space="preserve">Abstract</x> Unsuccessful anesthesia of the inferior alveolar nerve (IAN) may be due to supplementary innervations of mandibular molars from other branches, namely the cervical plexus (CP). The purpose of this prospective, randomized, double‐blind, controlled trial was to determine the effectiveness of an intraoral cervical plexus anesthetic technique (ICPAT) in mandibular molars with symptomatic irreversible pulpitis (SIR) when the IAN and lingual nerve (LN) blocks failed, and to provide a description of the technique. Forty patients diagnosed with SIR received IAN and LN block anesthesia prior to treatment. After clinical signs of anesthesia, patients were subjected to an electrical pulp test (EPT) at 2‐min cycles for 10 min post‐injection. The anesthesia was considered unsuccessful if there was a positive EPT response ten minutes following profound lip numbness. The experimental group (n = 20) were administered 2% Lidocaine with 1:100, 000 epinephrine using the ICPAT. The control group (n = 20) were administered 0.9% sterile saline using the ICPAT. Success was defined as no response on two consecutive readings from an EPT. In the experimental group, 60% of subjects showed successful anesthesia, whereas none of the subjects in the control group had successful anesthesia. A multiple logistic regression analysis showed that the anesthesia success rate using the ICPAT method was significantly higher (P < 0.05) than in the control group, irrespective of molar tooth type. The ICPAT method may be useful as a supplementary anesthetic technique for mandibular molars with SIR in subjects whom the IAN and LN blocks do not provide adequate anesthesia. Clin. Anat. 28:608–613, 2015. © 2015 Wiley Periodicals, Inc.